CONTENT VALIDITY OF ARABIC LEARNING QUALITY INSTRUMENTS USING EXPERT JUDGMENT AND AIKEN'S V - Nurul Hidayah; Farihin; Ahmad (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to analyze the validity of the content of the Arabic language learning quality instrument at Madrasah Tsanawiyah using an expert judgment assessment with the Aiken's V index. This study uses a quantitative approach with the type of instrument development research. The instrument developed was in the form of a Likert scale questionnaire consisting of 25 statements based on indicators of learning planning, learning implementation, use of learning media, teacher-student interaction, and student learning motivation. The validation of the instrument was carried out by four validators who have competence in the field of Arabic language learning and educational evaluation. The data from the validator assessment was analyzed using the Aiken's V index to determine the level of validity of the content of each instrument item. The results showed that the validity value of the instrument's contents was in the range of 0.312 to 1.000 with an average of 0.625. Most of the instrument items are in the valid and very valid category, although there are some items that need revision. These results show that the Arabic learning quality instrument developed has good content validity and is suitable for use in educational research. This research contributes to the development of Arabic learning quality instruments at the tsanawiyah madrasah level through an expert judgment based content validity approach and Aiken's V analysis which is still relatively limited found in previous research. The results of this study are expected to be useful for education researchers, Arabic teachers, and research instrument developers as a reference in the development of valid and systematic Arabic learning quality measurement tools.